Learning Ruby - Fitzgerald, Michael, 1957- (O'Reilly, 2007)
"You don't have to know everything about a car to drive one, and you don't need to know everything about Ruby to start programming with it. Written for both experienced and new programmers alike, Learning Ruby is a just-get-in-and-drive book - a hands-on tutorial that offers lots of Ruby programs and explains how and why they work, just enough to get you rolling down the road." "Interest in Ruby stems from the popularity of Rails, the web development framework that's attracting new devotees and refugees from Java and PHP. But there are plenty of other uses for this versatile language. The best way to learn is to just try the code. You'll find examples on nearly every page of this book that you can imitate and hack."--Jacket